(untitled) (TAJ: Journal of Teachers Association, 2020)
Context: LSTR 3 Mix MP therapy is one of the procedures for the management of nonvital tooth with periapical lesion. The principle of this therapy is the complete sterilization of the total pulp canal space, thereby healing of the periradicular lesion. Objectives: To assess the clinical and radiological outcome of ‘Lesion sterilization and Tissue Repair’ (LSTR) for endodontic treatment of nonvital teeth with periapical lesion. Materials and Methods: This descriptive, observational study allocated 40 nonvital teeth with periapical lesion treated by LSTR 3 Mix MP Therapy. In study subjects, a mixture of Metronidazole, Ciprofloxacin and Minocycline (3 Mix) in a proportion of 1:1:1 in ointment (Macrogol mixed with propylene glycol: MP) was placed at the orifice of the root canal or the bottom of pulp chamber after gaining access in the pulp chamber and removal of necrotic pulp, then sealed with Glass Ionomer cement and further reinforced by composite resin. The protocols for follow up examination were 3, 6 and 12 months post operatively. At the time of follow up examination a standard follow up chart was maintained. Results: Out of 40 cases, in 29 cases had good responses both clinically and radiologically and 8 patients came back with some complications. Out of these 8 patients, 6 patients had uncertain outcome and in 2 patients it was unacceptable. Conclusion: LSTR 3 mix MP therapy reduced clinical signs and symptoms successfully in teeth with periapical lesion and radiological improvement of the periapical index was also noted. TAJ 2020; 33(2): 76-84